Numerical simulation and experimental study on effect of cooling rate on microstructure and strength of nanostructured materials - Nguyen, Hai; Le, Duc; Hoang, Quyen; Quang, Pham (Vietnam Journal of Science and Technology, 2024)
In this study, by numerical simulation (finite element method, FEM) and experimental, the cooling rate was investigated by changing the product thickness (20, 3, 2, 1, 0.5 and 0.3) mm of Al based two-phase nanostructured materials casted through a copper mold. The effect of cooling rate on the microstructure and strength of the alloy was studied. The Experimental results showed that the precipitated intermetallic phases have a decreasing size corresponding to the increasing cooling rates by simulation from 102 K/s to 104 K/s. The results show that an appropriate cooling rate can improve the microstructure and properties of the alloy. The Abaqus/Standard capability for uncoupled heat transfer analysis was intended to model solid body heat conduction with general, temperature-dependent conductivity; internal energy (including latent heat effects); and quite general convection and radiation boundary conditions. This study describes the basic energy balance, constitutive models, boundary conditions, finite element discretization, and time integration procedures used. The time step used an automatic algorithm through the smallest tolerance. The maximum temperature change was allowed over a period and the increment was adjusted for this parameter, as was the rate of convergence in the non-linear cases. First-order heat transfer elements used the rule of numerical integration with integrated stations located at the corners of the element for thermal capacitance terms. (Jacobian terminology). This approach is particularly effective when there is a strong latent thermal effect. Thus, first - order elements were used in the case of latent heat. The HEATCAP element is available for single - point pooled thermal capacitance modeling. Centralized film loading options between the mold and the casting were specified by the user.